2016
DOI: 10.1136/jech-2016-207890
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the relationship between socioeconomic status and cardiovascular disease: a systematic review and meta-analysis

Abstract: Reduction of socioeconomic inequalities in CHD and CVD outcomes might require different approaches for men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
111
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(146 citation statements)
references
References 38 publications
16
111
3
4
Order By: Relevance
“…We were not able to corroborate the results of a recent review that revealed an overall stronger relationship between SES and cardiovascular outcomes among women compared with men 7. In the present study, the association was positive but weaker (not significant) among women compared with men.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We were not able to corroborate the results of a recent review that revealed an overall stronger relationship between SES and cardiovascular outcomes among women compared with men 7. In the present study, the association was positive but weaker (not significant) among women compared with men.…”
Section: Discussioncontrasting
confidence: 99%
“…Income and education are often used interchangeably, although they can tap into different proximate determinants of health 5 6. The relationship between SES and cardiovascular outcomes has also been reported to vary according to sex 7. Compared with cardiovascular disease in general, only a few studies have focused on the association between SES and survival after OHCA.…”
Section: Introductionmentioning
confidence: 99%
“…Comorbid health conditions in conjunction with depressive symptoms were significantly associated with perceived stress. Psychosocial stressors hypothesized to increase CVD risk in women, particularly middle aged and older women include low socioeconomic status, inadequate social support and financial insecurity (2123). …”
Section: Introductionmentioning
confidence: 99%
“…The higher response rate of males in the current study, secondary to the larger proportion of males invited, may reflect public opinion that CVD is a predominantly male disease despite also being the leading cause of death in females [5, 40]. Previous studies assessing participation in trials of those who already have CVD [41, 42], and in a survey regarding cardiovascular risk factors [43], also found lower response in females.…”
Section: Discussionmentioning
confidence: 62%
“…Modifiable risk factors for CVD include tobacco use, physical inactivity, obesity and raised low-density lipoprotein (LDL) cholesterol [24]. Those most at risk are older males, of south Asian ethnic background, with lower educational attainment and lower socioeconomic status [5, 6]. Lifestyle intervention trials for primary prevention of CVD are a research priority [7–9], but previous trials have reported low participation rates [10, 11].…”
Section: Introductionmentioning
confidence: 99%